Genome-Wide Identification and Characterization of Hexokinase Genes in Moso Bamboo (Phyllostachys edulis) - Zheng, Wenqing; Zhang, Yuan; Zhang, Qian; Wu, Ruihua; Wang, Xinwei; Feng, Shengnian; Chen, Shaoliang; Lu, Cunfu; Du, Liang (Frontiers in Plant Science, 2020)
Plant hexokinases (HXKs) are a class of multifunctional proteins that not only act as the enzymes required for hexose phosphorylation but also serve as sugar sensors that repress the expression of some photosynthetic genes when internal glucose level increases and regulators of cell metabolism and some sugar-related signaling pathways independent on their catalytic actives. The HXKs have been studied in many plants; however, limited information is available on HXKs of moso bamboo (Phyllostachys edulis). In this study, we identified and characterized 12 hexokinase genes in moso bamboo. Phylogenetic analysis revealed that the moso bamboo hexokinases (PeHXKs) were classifiable into five subfamilies which represented the three types of hexokinases in plants. Gene structure and conserved motif analysis showed that the PeHXK genes contained diverse numbers of introns and exons and that the encoded proteins showed similar motif organization within each subfamily. Multiple sequence alignment revealed that the PeHXK proteins contained conserved domains, such as phosphate 1 (P1), phosphate 2 (P2), adenosine, and a sugar-binding domain. Evolutionary divergence analysis indicated that the PeHXK, OsHXK, and BdHXK families underwent negative selection and experienced a large-scale duplication event approximately 19–319 million years ago. Expression analysis of the PeHXK genes in the leaf, stem, root, and rhizome of moso bamboo seedlings indicated that the PeHXKs perform pivotal functions in the development of moso bamboo. A protein subcellular localization assay showed that PeHXK5a, PeHXK8, and PeHXK3b were predominantly localized in mitochondria, and PeHXK8 protein was also detected in the nucleus. The HXK activity of the PeHXK5a, PeHXK8, and PeHXK3b was verified by a functional complementation assay using the HXK-deficient triple-mutant yeast strain YSH7.4-3C (hxk1, hxk2, and glk1), and the results showed that the three PeHXKs had the plant HXK-specific enzyme traits. The present findings would provide a foundation for further functional analysis of the PeHXK gene family.